Expression Pattern and Functional Characterization of PISTILLATA Ortholog Associated With the Formation of Petaloid Sepals in Double-Flower Eriobotrya japonica (Rosaceae) - Xia, Yan; Shi, Min; Chen, Weiwei; Hu, Ruoqian; Jing, Danlong; Wu, Di; Wang, Shuming; Li, Qingfen; Deng, Honghong; Guo, Qigao; Liang, Guolu (Frontiers in Plant Science, 2020)
Double-flower Eriobotrya japonica, of which one phenotype is homeotic transformation of sepals into petals, is a new germplasm for revealing the molecular mechanisms underlying the floral organ transformation. Herein, we analyzed the sequence, expression pattern and functional characterization of EjPI, which encoded a B-class floral homeotic protein referred to as PISTILLATA ortholog, from genetically cognate single-flower and double-flower E. japonica. Analysis of protein sequence alignments showed that EjPI has typical domains of MADS, I, K and C, and includes a distinctive PI motif at the C-terminal region. Phylogenetic analysis suggested that the EjPI gene was assigned to the rosids euPI lineage. Subcellular localization of EjPI was determined to be in the nucleus. Expression pattern analysis revealed that EjPI expressed not only in petals, filament and anther in single-flower E. japonica, but also in petaloid sepals in double-flower E. japonica. Meanwhile, EjPI expression was closely correlated with the homeotic petaloid sepal, and the expression level was positively related to petaloid sepal size within a sepal. Furthermore, 35S::EjPI transgenic wild-type Arabidopsis caused the homeotic transformation of the first whorl sepals into petaloid sepals. Ectopic expression of EjPI in transgenic pi-1 mutant Arabidopsis rescued normal petals and stamens. These results suggest expression pattern of EjPI is associated with the formation of petaloid sepal. Our study provides the potential application of EjPI for biotechnical engineering to create petaloid sepals or regulate floral organ identity in angiosperms.